1992
DOI: 10.1111/j.1348-0421.1992.tb01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Mouse Model of Cystitis and Roles of Type 1 Fimbriated Escherichia coli in Its Pathogenesis

Abstract: The role of type 1 fimbriae in promoting bladder colonization and the course of Escherichia coli cystitis were examined with type 1 fimbriated strains of clinically isolated E. coli. In the experiments of mice in vivo, intact bladder epithelium showed natural resistance to the adherence of type 1 fimbriated and nonfimbriated E. coli. However, the exfoliation of bladder superficial cells by trypsinization before the bacterial inoculation promoted the adhesion and colonization of type 1 fimbriated E. coli onto b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Although others have assessed the interaction of E. coli strains and mouse bladder (1,5,8,21) or the development of cystitis and pyelonephritis following experimental challenge of mice or nonhuman primates with E. coli (16,31,32), this is the first study to assess differences between the uropathogenicities of pyelonephritis and cystitis strains of E. coli in an animal model of UTI. We chose to use the transurethrally challenged mouse model which was originally described by Hagberg et al (9), who documented that a P-fimbria-expressing strain colonized the kidney better than P-fimbria-negative strains.…”
Section: Discussionmentioning
confidence: 99%
“…Although others have assessed the interaction of E. coli strains and mouse bladder (1,5,8,21) or the development of cystitis and pyelonephritis following experimental challenge of mice or nonhuman primates with E. coli (16,31,32), this is the first study to assess differences between the uropathogenicities of pyelonephritis and cystitis strains of E. coli in an animal model of UTI. We chose to use the transurethrally challenged mouse model which was originally described by Hagberg et al (9), who documented that a P-fimbria-expressing strain colonized the kidney better than P-fimbria-negative strains.…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al [19] reported that removal of superficial cells was essential for the adherence of type 1 fimbriated E. coli to the bladder epithelia. In contrast, our results showed that the superficial cells in the infected bladders were not desquamated, but stained strongly or interme diately positive for almost all lectins, especially for Con A.…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, various proton pump inhibitors in 20 ul PBS were injected into the bladder lumen via the urethra [12], and then time courses of the urinary pH were followed.…”
Section: Measurement Of Urinary Phmentioning
confidence: 99%